Patent regime shift and firm innovation strategy: Evidence from the Second Amendment to China's Patent Law - Tong, Tony W.; He, Wenlong; Chen, Liang; He, Zi‐Lin; Lu, Jiangyong (Strategic Management Journal, 2026)
Abstract Research Summary While changes in intellectual property rights (IPR) protection significantly shape firm innovation, the mechanisms driving firms' responses remain poorly understood. Leveraging the Second Amendment to China's Patent Law, which strengthens appropriability particularly for state‐owned enterprises (SOEs), as a natural experiment, we show that stronger IPR has mixed effects on SOEs' innovation. While SOEs increase the rate of innovation subsequent to the Amendment, they shift the direction of innovation toward more familiar areas in which they face a lesser need to adjust existing routines. This directional change suggests a quality decline in SOEs' innovation that may be attributed to path dependence. We further show that this change varies systematically depending on different firm‐ and industry‐level characteristics that loosen or tighten the historical grip of path dependence. Managerial Summary This study offers valuable insights for corporate leaders navigating intellectual property rights (IPR) reforms and shaping their firms' innovation strategies, particularly in emerging economies. While stronger IPR protection can increase innovation output, it may also lead firms to concentrate on familiar technologies rather than pursue more novel ideas. Thus, corporate leaders should look beyond patent volume as a performance metric and instead foster creative thinking and engage in external collaborations to access new, cutting‐edge knowledge. Such efforts can help firms move beyond established routines and strengthen their long‐term competitiveness. To promote innovation of greater novelty, policymakers must complement stronger IPR protection with broader institutional support, including enhancing economic freedom, encouraging market competition, and cultivating a culture that values breakthrough innovation.